The Role of the Prader-Willi Syndrome Critical Interval for Epigenetic Regulation, Transcription and Phenotype - Simona Zahova; Anthony R. Isles (Epigenomes, 2018)
Prader-Willi Syndrome (PWS) is a neurodevelopmental disorder caused by loss of expression of the paternally inherited genes on chromosome 15q11.2-q13. However, the core features of PWS have been attributed to a critical interval (PWS-cr) within the 15q11.2-q13 imprinted gene cluster, containing the small nucleolar RNA (snoRNA) SNORD116 and non-coding RNA IPW (Imprinted in Prader-Willi) exons. SNORD116 affects the transcription profile of hundreds of genes, possibly via DNA methylation or post-transcriptional modification, although the exact mechanism is not completely clear. IPW on the other hand has been shown to specifically modulate histone methylation of a separate imprinted locus, the DLK1-DIO3 cluster, which itself is associated with several neurodevelopmental disorders with similarities to PWS. Here we review what is currently known of the molecular targets of SNORD116 and IPW and begin to disentangle their roles in contributing to the Prader-Willi Syndrome phenotype.